Optimization of stocking density of Labeo rohita and Cirrhinus mrigala spawn in relation to water quality, survival and growth under recirculating system - SHARMA, JAI GOPAL; KUMAR, SUNIL; CHAKRABARTI, RINA (The Indian Journal of Animal Sciences, 2014)
The effect of stocking density on the survival and growth of Labeo rohita (rohu) and Cirrhinus mrigala (mrigal) wasevaluated under recirculating systems. Indian major carp rohu (1.0Â±0.002 mg) and mrigal (1.0Â±0.002 mg) spawns werecultured separately at 3 different stocking densities of 100, 125 and 150 larvae 15 litre aquarium. Survival was significantly(P